ANALISIS BAURAN PEMASARAN 4P PADA DESTINASI WISATA DESA WISATA BAGOT KABUPATEN SAMOSIR - Siahaan, Sondang Beatrix; Simbolon, Novi Handayani; Pasaribu, Ika Mary (Bisnis-Net, 2024)
Marketing allows tourism destinations to attract attention and create attraction for potential tourists, create a positive image, and differentiate themselves from other destinations. Tourism has a strategic role in increasing the economic growth of a region, as well as providing a positive impact on local development. In this article, the object studied is the Bagot Tourism Village which is located in Samosir Regency. The aim of this research is to analyze the marketing mix (product, price, promotion, and place). This research aims to conduct an in-depth study of the marketing mix in Bagot Tourism Village, located in Samosir Regency, by analyzing the 4P marketing mix (products, prices, promotions, and places/distribution channels) in the Bagot Tourism Village. The research was conducted using descriptive qualitative analysis methods. Research data was collected by conducting observations in the Bagot Tourism Village and interviews with the head of the POKDARWIS (Kelompok Sadar Wisata) as the manager of the Bagot Tourism Village, as well as documentation studies. The research results show that Bagot Tourism Village as a tourism destination in Samosir Regency in marketing activities pays great attention to the 4Ps (product, price, promotion, and place) especially product, price, and place. There is still room to further improve promotions, especially through social media. Bagot Tourism Village not only sells products, but also plays an active role in introducing and preserving local culinary traditions. This provides significant added value and is one of the main competitive advantages of Bagot Tourism Village.